2012
DOI: 10.1029/2011tc003010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical versus kinematical shortening reconstructions of the Zagros High Folded Zone (Kurdistan region of Iraq)

Abstract: [1] This paper compares kinematical and mechanical techniques for the palinspastic reconstruction of folded cross sections in collision orogens. The studied area and the reconstructed NE-SW trending, 55.5 km long cross section is located in the High Folded Zone of the Zagros fold-and-thrust belt in the Kurdistan region of Iraq. The present-day geometry of the cross section has been constructed from field as well as remote sensing data. In a first step, the structures and the stratigraphy are simplified and sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…For the Murtèl rockglacier, the 2D approximation is justified because of its straight tongue‐like geometry and unidirectional flow field (Kääb et al, ). Details of the numerical technique can be found in Frehner and Schmalholz (); Frehner () and Frehner et al (), who all applied variations of this model to simulate viscous buckle folding under kinematic layer‐parallel forcing. In the present model, the rockglacier flows solely under the effect of gravity.…”
Section: Methodsmentioning
confidence: 99%
“…For the Murtèl rockglacier, the 2D approximation is justified because of its straight tongue‐like geometry and unidirectional flow field (Kääb et al, ). Details of the numerical technique can be found in Frehner and Schmalholz (); Frehner () and Frehner et al (), who all applied variations of this model to simulate viscous buckle folding under kinematic layer‐parallel forcing. In the present model, the rockglacier flows solely under the effect of gravity.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have demonstrated that the characteristics and the wavelength of folding in fold-and-thrust belts are strongly influenced by rheological parameters and 2014 mechanical isotropies of the stratigraphic pile (Yamato et al, 2011;Ruh et al, 2012). Therefore, future research will focus on mechanical reconstructions of fold-and-thrust belts (Simpson, 2009;Frehner et al, 2012;Vidal-Royo et al, 2012) including three-dimensional mechanical interaction of fold and fault growth (Schmid et al, 2008a;Grasemann and Schmalholz, 2012). (iii) A crystalline core zone forms the central and highest part of a mountain belt, usually above the orogenic root, where the crust is the thickest.…”
Section: Anatomy Of Orogens: the Critical Partsmentioning
confidence: 95%
“…The study area is located in Zagros high folded zone from sedimentary-structural classification point of view [14]. Due to the specific tectonic conditions, this area consists of the crushed rock masses of gypsum, limestone, mudstone, sandstone, shale and marlstone.…”
Section: Geological Setting and Geotechnical Propertiesmentioning
confidence: 99%